What Keeps Kids Coming Back? Retention in a Sport-Based Positive Youth Development Program - Dawn Anderson-Butcher; Anthony J. Amorose; Claire Sobecki; Travis R. Scheadler; Obidiah Atkinson; Emily Gutzwiller (Frontiers Media S.A., 2022)
Research finds engagement in sport-based positive youth development (PYD) programs contribute to key outcomes related to physical, social, emotional, cognitive, and mental health. Consistent, long-term participation ensures youth, especially those who are socially vulnerable, reap the most benefits. Even when common barriers are removed, retention remains a challenge. Using mixed methods, this study explored factors related to long-term retention among youth from socially vulnerable circumstances attending one sport-based PYD program. Factors related to youth participation in the previous year's program, as well as general youth demographics, were examined using difference tests and binomial logistic regression to explore retention among 124 of the 384 youth who returned to the program the following year. Results of the regression analyses showed the full model (with all predictors included), vs. an intercept-only model, was statistically significant, χ2 (11, N = 235) = 23.38, p = 0.02. The model correctly classified 88.2% of the non-returners and 28.0% of the returners for an overall correct classification rate of 67.2%. Better fitness levels, higher perceived social responsibility (an outcome targeted in the program), and some demographic variables (such as lower poverty rates and younger age) were associated with a greater probability of returning, although effect sizes were small. Additionally, interviews were conducted with 18 parent/caregivers of returning youth and 18 match comparison parent/caregivers of non-returning youth. Qualitative analyses revealed few differences in previous year's program experiences between returners and non-returners, as well as similarities in reported benefits from involvement. Both sets of parent/caregivers cited positive experiences overall, and particular benefits related to meeting new people and learning new sports. Parents/caregivers of non-returners, however, noted the value of physical literacy components of the program more so than their counterparts. Social interactions, both positive and negative, seem to have particular relevance for retention. Findings overall, however, demonstrate challenges with predicting retention and fostering long-term engagement among youth from socially vulnerable circumstances in programming.